Occupational Exposure to Talc Increases the Risk of Lung Cancer: A Meta-Analysis of Occupational Cohort Studies. (31st August 2017) - Chang, Che-Jui; Tu, Yu-Kang; Chen, Pau-Chung; Yang, Hsiao-Yu
Abstract : Objective . Talc is widely used in industrial applications. Previous meta-analyses of carcinogenic effects associated with inhaled talc included publications before 2004, with a lack of data in China, the largest talc-producing country. The safety of workers exposed to talc was unclear due to limited evidence. The objective of this study was to reevaluate the association between inhaled talc and lung cancer. Setting, Participants, and Outcome Measures . A meta-analysis was performed to calculate the meta-SMR of lung cancer. We searched the MEDLINE, EMBASE, CNKI, and Wanfang Data databases through March 2017. Data from observational studies were pooled using meta-analysis with random effects models. Results . Fourteen observational cohort studies (13 publications) were located via literature search. The heterogeneity of the included data was high (I -squared = 72.9%). Pooling all the cohorts yielded a meta-SMR of 1.45 (95% CI: 1.22–1.72, p < 0.0001 ) for lung cancer among the study subjects exposed to talc. Subgroup analysis for asbestos contamination showed no significant difference in lung cancer death between subjects exposed to talc with and without asbestos ( p = 0.8680 ), indicating that this confounding factor may have no significance. Conclusions . This study provides evidence that nonasbestiform talc might still increase the risk of lung cancer. Further epidemiological studies are required to evaluate the safety of workers with occupational talc exposure.